'Ecobordering': casting immigration control as environmental protection. Issue 1 (2nd January 2022) - Turner, Joe; Bailey, Dan
ABSTRACT: Based on an analysis of 22 European far-right parties, we identify an emergent discourse in environmental politics, which we conceptualise as 'ecobordering'. This discourse seeks to blame immigration for national environmental degradation, which draws on colonial and racialised imaginaries of nature in order to rationalise further border restrictions and 'protect' the 'nativist stewardship' of national nature. As such, ecobordering seeks to obscure the primary driving causes of the ecological crisis in the entrenched production and consumption practices of Global North economies, whilst simultaneously shifting blame on to migration from the Global South where ecological degradation has been most profound. In an era of increasing climate migration, ecobordering thereby portrays effects as causes and further normalises racist border practices and colonial amnesia within Europe.